ANALISIS IMPLEMENTASI NILAI-NILAI PANCASILA DAN PENGUATAN KARAKTER PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI UPTD SD NEGERI KENARILANG - Loin Esi M. Hamap; Antonius A. Saetban; Yessy Mata (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Hamap. M Esi Loin.22586026068. This research was motivated by the importance of implementing Pancasila values in strengthening the character of elementary school students. Although Pancasila values had been applied in the learning process in Class V of UPTD SD Negeri Kenarilang, some students still demonstrated behaviors inconsistent with these values, such as disturbing friends during prayer, not respecting peers' opinions, being undisciplined, and cheating during assignments. This research aims to determine how Pancasila values are implemented in strengthening student character in Pancasila Education subject for Class V at UPTD SD Negeri Kenarilang. The research used a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. Research subjects were the Class V homeroom teacher and 27 Class V students. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing, with data validity through technical triangulation. The results showed that the implementation of Pancasila values in strengthening student character had been carried out quite well through habituation, exemplary conduct, group discussions, cooperation, and extracurricular activities. The First Principle was applied through regular prayer and religious tolerance; the Second Principle through mutual assistance and respect; the Third Principle through group cooperation and mutual cooperation; the Fourth Principle through class discussions and deliberation; and the Fifth Principle through responsibility and honesty. The main challenges were students' lack of awareness, environmental influences, and insufficient family support. The teacher addressed these challenges through the 7 Habits of Great Indonesian Children Program, providing guidance, and cooperating with parents.